TEKNOLOGI PAKAN KUCING OTOMATIS DENGAN SISTEM BUKA TUTUP MENGGUNAKAN DINAMO, SERVO, DAN SENSOR LIMIT SWITCH BERBASIS ARDUINO UNO - Mukhlison; Sri Widoretno; Iftah Anjani Putra (Universitas Islam Balitar Blitar, 2024)
Pet welfare is a human right that belongs to the animal itself. However, this does not get enough attention from the public or pet owners. Judging from the owner's lack of knowledge of the pets they own and the lack of facilities that support the welfare of the pets themselves. Inefficient and ineffective feeding of cats will affect the animal's diet. Because irregular eating patterns can cause digestive disorders in cats. For this reason, an automatic mechanism is needed that can be used to help feed pets according to the right time and dose. So that this final project will design and build an Automatic Cat Feeding Tool with an Open and Close System Using a Dynamo, Servo, and Sensor Limit Switch which is composed of several connected programs and is based on Arduino Uno. With the existence of an automatic cat feeding device, it is hoped that it can overcome the problems faced by cat owners. Apart from that, it can also save costs, increase the time and energy efficiency of cat owners, and can create a sense of calm for cat owners when leaving their pets at home even without full supervision